Reply to the offer about fire protecting coating at increased amount of BOQ item no.10.2 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reply to the offer about fire protection coating at increased quantity of BOQ item for BRACU new campus project.